TESS photometry of extreme helium stars PV Tel and V821 Cen. (29th April 2020) - Jeffery, C Simon; Barentsen, Geert; Handler, Gerald
ABSTRACT: PV Tel variables are extreme helium (EHe) stars known to be intrinsic light and velocity variable on characteristic time-scales of 0.1–25 d. With two exceptions, they are best described as irregular. Light curves have invariably been obtained from single-site terrestrial observatories. We present Transiting Exoplanet Survey Satellite observations of two bright EHe stars, Popper's star (V821 Cen) and Thackeray's star (PV Tel). PV Tel is variable on time-scales previously reported. V821 Cen is proven to be variable for the first time. Neither light curve shows any evidence of underlying regularity. Implications are considered.